Hindcasting Ecosystem Functioning Change in an Anthropogenized Estuary: Implications for an Era of Global Change - Fang, Xiaoyu; Cozzoli, Francesco; Smolders, Sven; Knights, Antony; Moens, Tom; Soetaert, Karline; Van Colen, Carl (Frontiers in Marine Science, 2021)
Ecosystem-based management requires a sound integration of how species populations influence ecosystem functioning across heterogeneous spatial and temporal scales. Here, we combined an empirically-derived metabolic model for the effect of the common ragworm Hediste diversicolor on sediment biogeochemistry (measured as sediment oxygen uptake) with a population biomass distribution model, to illustrate spatial and temporal patterns of change in ecosystem functioning in a large European estuary, the Western Scheldt. We hindcasted an overall decrease by 304 tons in ragworm biomass between 1955 and 2010, accounting for a reduction by 28 % in stimulated sediment oxygen uptake at the landscape scale. Local gains or losses in habitat suitability and ecosystem functioning were driven by hydrodynamic changes resulting from deepening, dredging and disposal practices, demonstrating the applicability for ecosystem management of our applied predictive framework to upscale past and anticipated population effects on ecosystem functioning.